2006
DOI: 10.1007/s10755-006-9027-3
|View full text |Cite
|
Sign up to set email alerts
|

Translating Comments on Student Evaluations into the Language of Learning

Abstract: Written comments on student evaluations often seem idiosyncratic, lacking the power of numerical statistical data. These statements, however, may sometimes reveal intellectual challenges common to novice learners in our disciplines. Instructors can use these insights as part of a scholarly approach to teaching, making meaningful adjustments to future classes and informing curricular choices in productive ways. In this article we examine common student complaints in three particular situations: quantitative cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…"Faculty look at the written comments for anecdotal insights and, as often as not, for confirmation of their own great performance" (Benton, 2011, p. 44). However, the findings prove the belief by Hodges and Stanton (2007) that, at times, negative written comments may result from a lack of student awareness about their own learning processes. Brock, Van Roy and Mortelmans (2012) found that "positive comments are almost always more specific…findings in the current study show that students seem to take SETs seriously…they almost always give valuable specific improvement aspects" (p. 1131).…”
Section: Chapter 5: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…"Faculty look at the written comments for anecdotal insights and, as often as not, for confirmation of their own great performance" (Benton, 2011, p. 44). However, the findings prove the belief by Hodges and Stanton (2007) that, at times, negative written comments may result from a lack of student awareness about their own learning processes. Brock, Van Roy and Mortelmans (2012) found that "positive comments are almost always more specific…findings in the current study show that students seem to take SETs seriously…they almost always give valuable specific improvement aspects" (p. 1131).…”
Section: Chapter 5: Discussionsupporting
confidence: 66%
“…The literature revealed that interpreting written comments can be difficult because they appear to be a series of random unconnected statements on instructors, their teaching, and the education environment (Brock, Van Roy & Mortelmans, 2012;Hodges & Stanton, 2007). The data confirmed that framing the secondary data using the Seven Principles was necessary and useful.…”
Section: Chapter 5: Discussionmentioning
confidence: 70%
See 3 more Smart Citations